2021
DOI: 10.4103/jfmpc.jfmpc_1496_20
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of E-cigarette uses among medical students at Umm Al-Qura University; a cross-sectional study 2020

Abstract: Background: Electronic cigarette (e-cigarette) is becoming increasingly popular worldwide, and commercially a commonplace in the media. Health concerns and the avoidance of smoking are the most frequently reported factors for conventional smokers to turn to e-cigarettes. However, there is insufficient information about the use of e-cigarettes in Makkah city; therefore, this study aims to determine the prevalence of electronic cigarette uses among medical students at Umm al-Qura University (UQU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…All of these facts likely contributed to the e-cigarette use among our students. Similarly, Other studies showed similar factors contributing to the widespread e-cigarette use in the Kingdom of Saudi Arabia [ 16 , 29 ]. Therefore, we should raise public awareness of the risks associated with e-cigarette use, especially among young adults.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…All of these facts likely contributed to the e-cigarette use among our students. Similarly, Other studies showed similar factors contributing to the widespread e-cigarette use in the Kingdom of Saudi Arabia [ 16 , 29 ]. Therefore, we should raise public awareness of the risks associated with e-cigarette use, especially among young adults.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to our research, Qanash et al found in a survey conducted in 2017 that the prevalence of e-cigarette use was 28% among health sciences college students in Jeddah [ 15 ]. Similarly, Alshanberi et al found in a survey conducted in 2020 a high prevalence of e-cigarette use among medical students at Umm al-Qura University, reaching up to 32% [ 16 ]. Aqeeli et al also found that the prevalence rate of e-cigarette use was 21% among students of Jazan University [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Jeddah revealed that the most common reason is entertainment, followed by peer effects [7]. Moreover, a study at Umm Al-Qura University showed that the most common reason for smoking e-cigarettes was the taste, followed by trying to quit smoking [20].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies (n=17) included in this review were conducted in Saudi Arabia [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]55 . The first study was conducted in 2014 (participants, n=3027).…”
Section: Prevalence and Awareness Of E-cigarettes In Arab Countries S...mentioning
confidence: 99%